1995
DOI: 10.1177/154193129503900125
|View full text |Cite
|
Sign up to set email alerts
|

Aurally Aided Detection and Identification of Visual Targets

Abstract: The experiments described in this report provide baseline performance measures of aurally directed detection and search for visual targets in an observer's immediate space. While the simple target detection task was restricted to the frontal hemi-field (extending 180 degrees in azimuth and 150 degrees in elevation), visual search performance (discrimination of which of two light arrays was present on a given trial) was evaluated for both the frontal and rear hemi-fields. In both tasks, the capacity to process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Our findings generally extend the previous findings of interactions between vision and audition in spatial perception (Arnott and Goodale 2005;Driver and Spence 1998;Razavi et al 2007) and specifically extend previous findings on aurally aided visual search (Perrott et al 1995(Perrott et al , 1996. Such studies typically show better accuracy and faster reaction times when auditory and visual stimuli are presented from the same relative to different locations across the horizontal plane.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings generally extend the previous findings of interactions between vision and audition in spatial perception (Arnott and Goodale 2005;Driver and Spence 1998;Razavi et al 2007) and specifically extend previous findings on aurally aided visual search (Perrott et al 1995(Perrott et al , 1996. Such studies typically show better accuracy and faster reaction times when auditory and visual stimuli are presented from the same relative to different locations across the horizontal plane.…”
Section: Discussionsupporting
confidence: 91%
“…For example, it is well known that the visual system can provide a spatial frame-of-reference which can facilitate the localisation of an auditory target along the azimuth (Alais and Burr 2004;Jackson 1953;Shelton and Searle 1980;Warren 1970). Similarly, an auditory stimulus can aid the detection of a visual stimulus when both are presented from the same spatial location (Perrott 1984;Perrott et al 1995;Spence 2007;Spence and Driver 2000). In particular, these studies showed an effect of spatial congruency by manipulating the relative locations of audio-visual stimuli along the horizontal plane only.…”
Section: Introductionmentioning
confidence: 99%
“…The AcE realm is vast in its expanse, and its physical dimensions are not easily delineated. There appears to be no lateral limit to AcE space, which completely encapsulates us in a 360° surround, as we can orient to auditory warning cues that even emanate from behind the head (Perrott, Cisneros, McKinley, & D'Angelo, 1995; Perrott, Saberi, Brown, & Strybel, 1990). However, visuospatial memory becomes distorted (compressed) outside of the visible FOV (Beer, 1993), normally extending to about 200°, and even auditory orienting becomes somewhat less effective behind the head (Perrott et al, 1995, 1990).…”
Section: Human Perceptual–motor Systems and Their Interaction With Th...mentioning
confidence: 99%
“…Once the source was located, the listener visually identified the target and responded. The target acquisition time was a salient measure of the quality of the localization cue 4,5,6,7,8 . The methodology used was an aurally guided visual search task with varied sound presentation levels.…”
Section: Introductionmentioning
confidence: 99%